STRATEGI KAMPANYE KOMUNIKASI PUBLIK INTERNAL (Studi Kasus Internal Public Awareness Campaign Badan Pemeriksa Keuangan Republik Indonesia melalui Media Digital Signage Priode Tahun 2013) - , Veni Friyanti, Drs. Kuskridho Ambardi, MA., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Financial Investigation Bureau (BPK) is in the process of good governance implementation. However, in fact, public perceptions state that BPKâs employees are less discipline and varied in the implementation of basic values of BPK and the management of published issues. BPK is suggested to improve proactive and responsive actions in conveying information to stakeholders. In this regard, BPK conducts internal campaign in Internal Public Awareness Campaign (Internal PAC) Program. This campaign is the suggestion to develop relationship between BPK and its employees so it can support the existence of organization. Campaign strategy implemented through research stages such as problem identification, planning and programming, implementation, monitoring and evaluation. This research uses qualitative approach and case study method by matching patterns to analyze data based on the existing theories. The results of the research show that planning activity as the reference of campaign implementation, i.e. to disseminate information and formulate campaign strategy and increase campaign effectiveness. The campaign done with digital signage media needs to do public segmentation because every employee in BPK has different background and experiences. Besides, without outcome evaluation from the implementation of Internal PAC, the planned purposes cannot be assessed. While supporting factors of internal campaign, especially in public organization is support from the leader through his/her policy. Other than that, it is necessary to pay attention to the message conveyed in order to make it easier to be understood, interesting and internalized to be the employeesâs belief.